Explaining congressional-presidential relations : a multiple perspectives approach - Shull, Steven A. (SUNY series in the presidency., 1999)
Provides a multivariate analysis of presidential-congressional interaction. Explaining Congressional-Presidential Relations examines government activities involving direct interactions between presidents and Congress and considers whether they are influenced by executive, legislative, and/or exogenous factors. The book encompasses presidential position taking on legislative votes, legislative support of presidents'positions, presidents'propensity to veto legislation, and budget agreement between the two branches, all of which are elements in the adoption of public policy -- Provided by publisher